ANCAMAN SAMPAH PLASTIK PADA BIOTA LAUT DALAM SENI RUPA MIX MEDIA - Qoyyuumu, Sulistia; Mudjiati (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
This research aims to explore the concept of plastic waste and other forms of waste—such as fashion waste and medical waste—as the foundation for creating mixed-media fine art. The method employs a pragmatic artistic interest approach with a semi-figurative style, using zinc as the primary medium alongside painting techniques like plakate, impasto, pointillism, and brushstrokes. The creative process began by collecting used medical plastic waste, including infusion bottles, oxygen masks, NGT tubes, and medicine packaging, which were then collaged and integrated into a two-dimensional artwork. The result is a mixed-media fine art piece that holds not only aesthetic value but also conveys a powerful environmental message about ocean pollution caused by plastic waste.